Optimal pulse width modulation for permanent magnet synchronous motor drive with improved torque and thermal losses using pulse numbers. Issue 1 (1st July 2022) - Viswanathan, Tamilarasu; Prabhakaran, Anush; Sekar, R M; Rajan Babu, W; Mathankumar, M; Gowdham Kumar, S
Abstract: This paper utilises the concept of pulse numbers to provide a new optimal pulse width modulation strategy for permanent magnet synchronous motor operation. The benefits of traditional modulation systems are preserved, as is an improvement in torque and thermal loss reduction. The continuous modulation approaches' performance limitations are solved by separating the performance constraints based on the drives surface area. The rotating component, which is regulated through odd and even pulse numbers, is used to mimic torque and thermal losses. With increases to 20 rpm and 30 rpm speeds, the suggested methods boost the 6% to 8% line current. Thermal losses are reduced by 21° C to 23° C, and torque is improved by 2 to 4 Nm. The proposed system is implemented by creating a MATLAB model that ensures the theoretic concept.